2001
DOI: 10.1076/apab.109.1.80.4279
|View full text |Cite
|
Sign up to set email alerts
|

Age-Related Changes in the Synapses of the Rat' Neostriatum

Abstract: By means of transmission electron microscopy, the age-related changes in axospinous (ASS) and axodendritic (ADS) synapses in the dorsal part of the rostral neostriatum in two groups of Wistar rats: young (3-month-old), and senescent (25-month-old) were examined. The changes in different parameters, characterizing the ASS and ADS: synaptic density (SD), number of synaptic vesicles (SV), number of synaptic contact zone (SCZ), and number of dendritic spines, bearing synapses (DS) were investigated morphometricall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…In the present study, we extended this finding to include the presynaptic compartment, and showed a proportional increase in axon terminal diameter. Similar increases in axon terminal size have been previously described in the neostriatum and cortex of aged rodents (Itzev, Lolova, Lolov, & Usunoff, ; Mostany et al, ). Age‐dependent alterations to morphology, such as swelling, could potentially contribute to axon terminal enlargement (Cork et al, ; Peters & Sethares, ).…”
Section: Discussionsupporting
confidence: 83%
“…In the present study, we extended this finding to include the presynaptic compartment, and showed a proportional increase in axon terminal diameter. Similar increases in axon terminal size have been previously described in the neostriatum and cortex of aged rodents (Itzev, Lolova, Lolov, & Usunoff, ; Mostany et al, ). Age‐dependent alterations to morphology, such as swelling, could potentially contribute to axon terminal enlargement (Cork et al, ; Peters & Sethares, ).…”
Section: Discussionsupporting
confidence: 83%
“…In fact, it should be noted that the volume and amount of protein associated with nerve terminals is expected to be several‐fold lower than other neuronal compartments like dendrites (Rusakov et al . 1998; Itzev et al . 2001).…”
Section: Discussionmentioning
confidence: 99%
“…However, the observation that there was a lower density of A 2A and mGluR5 receptors located in glutamatergic nerve terminals does not necessarily mean that the modulation of glutamate release by A 2A and mGluR5 receptors might represent a minor action of these receptors in the striatum. In fact, it should be noted that the volume and amount of protein associated with nerve terminals is expected to be several-fold lower than other neuronal compartments like dendrites (Rusakov et al 1998;Itzev et al 2001). Therefore, when considering receptors that are located both pre-and postsynaptically, it is always expected that they should be more abundant postsynaptically because of the larger volume showing that there is a co-localization of mGluR5 and A 2A receptors in nearly 50% of the glutamatergic nerve terminals (identified as vGluT1 and vGluT2 immunoreactive).…”
Section: Discussionmentioning
confidence: 99%